STUDI ORGANOLOGI ALAT MUSIK GISINT DAN BONSI DALAM UPACARA ADAT BEBUKUKNG SUKU DAYAK LINOH KABUPATEN SINTANG - Kudun, Oktavanus; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research is backgrounded by the uniqueness of Gisint and Bonsi musical instruments so that the researcher needs to examine the organology of the instruments. This study is aimed at describing the structures, the making process the way how to play the Gisint and Bonsi musical instrument in Bebukukng traditional ceremony of Linoh Dayak tribes of Sintang District. Qualitative descriptive method and organology approach were used in this study. The data in this research were obtained from field observation and interview with the informants who are expert in structure, making process, and playing the Gisint and Bonsi musical instrumental in Bebukukng traditional ceremony of Linoh Dayak Tribe of Sintang District. The data were analyzed qualitatively from the interviewees such as Mr Dandui, Mr Idi, Mr Apolonius Inci and several artists who understand about Bebukukng music, especially the organology of Gisint and Bonsi musical instrument in Bebukunkg traditional ceremony of Linoh Dayak Tribe of Sintang District. Based on the data analysis, it was concluded that Gisint and Bonsi musical instruments are parts of a tradition, in which they are made from bamboo. The Gisint musical instrument is made from the dried bamboo stem with the size of an adult people’s arm, as well as Bonsi musical instrument is made from one segment of bamboo stick with the size of an adult’s thumb. Keywords: Bebukukng, Gisint and Bonsi, Linoh Dayak Tribe, Sintang District